2021
DOI: 10.1186/s13071-021-05076-8
|View full text |Cite
|
Sign up to set email alerts
|

Beech tree masting explains the inter-annual variation in the fall and spring peaks of Ixodes ricinus ticks with different time lags

Abstract: Background The tick Ixodes ricinus is an important vector of tick-borne diseases including Lyme borreliosis. In continental Europe, the nymphal stage of I. ricinus often has a bimodal phenology with a large spring peak and a smaller fall peak. There is consensus about the origin of the spring nymphal peak, but there are two alternative hypotheses for the fall nymphal peak. In the direct development hypothesis, larvae quest as nymphs in the fall of the same year that they obtained their larval b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 97 publications
1
23
0
Order By: Relevance
“…The overall phenological patterns observed in our study followed a climatic gradient previously reported: (1) a unimodal pattern with a summer peak and a winter pause (Pattern 1) in freezing climates (Karelia, Russia); (2) a bimodal pattern with spring-autumn peaks (Pattern 2) in intermediate climates (European Russia's temperate zone); (3) a unimodal pattern with a late winter peak (Pattern 3) in warmer climates (Algeria) 18 . Also, a similar phenology trend observed in one mountain region in Switzerland was reported to follow an elevation gradient where the spring-autumn bimodal phenology (Pattern 2) shifted to a late-spring unimodal phenology (Pattern 1) at a higher elevation 17 , presumably due to a temperature gradient. A similar climatic trend was observed in Ixodes scapularis nymphs in a study conducted across a large geographic area in the United States, with peak nymph activity occurring in the summer in colder regions, and late spring in warmer regions 55 .…”
Section: Dispersion Parametersupporting
confidence: 78%
See 2 more Smart Citations
“…The overall phenological patterns observed in our study followed a climatic gradient previously reported: (1) a unimodal pattern with a summer peak and a winter pause (Pattern 1) in freezing climates (Karelia, Russia); (2) a bimodal pattern with spring-autumn peaks (Pattern 2) in intermediate climates (European Russia's temperate zone); (3) a unimodal pattern with a late winter peak (Pattern 3) in warmer climates (Algeria) 18 . Also, a similar phenology trend observed in one mountain region in Switzerland was reported to follow an elevation gradient where the spring-autumn bimodal phenology (Pattern 2) shifted to a late-spring unimodal phenology (Pattern 1) at a higher elevation 17 , presumably due to a temperature gradient. A similar climatic trend was observed in Ixodes scapularis nymphs in a study conducted across a large geographic area in the United States, with peak nymph activity occurring in the summer in colder regions, and late spring in warmer regions 55 .…”
Section: Dispersion Parametersupporting
confidence: 78%
“…However, previous studies on the effects of the environment on I. ricinus nymph activities in Europe did not capture all the aforementioned levels of variation. They largely focused on either a short-term period for multiple sites [21][22][23][24] or a long-term period for a few areas [14][15][16][17] . The present study attempted to explore the baseline abundance, seasonal, and inter-annual variations of I. ricinus nymph activity by expanding the observation across a wide range of geographical/climatic areas over a long period, involving a total 27,53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even applied to adult ticks, these curves can be compared to our predictions for the nymphal stage in Carquefou and Gardouch (oceanic and southwestern basin climate respectively), and in Saint-Genès-Champanelle (mountain climate), respectively. Concerning mountain climate, Bregnard et al (2021a) show a cline ranging from bimodal to unimodal curves when reaching higher altitude (altitude ranging from 620 to 1073 m). According to Gray et al (2016), I. ricinus abundance patterns for larvae, nymphs and adults follow a bimodal curve in Central and Western Europe, but these authors also point out that there are variations on this expert-based pattern.…”
Section: Discussionmentioning
confidence: 99%
“…mountain climate), respectively. Concerning mountain climate,Bregnard et al (2021a) show a cline ranging from bimodal to unimodal curves when reaching higher altitude (altitude ranging from 620 to 1073 m). According toGray et al (2016), I. ricinus abundance patterns for larvae, nymphs and adults follow a bimodal curve in Central and Western Europe, but these authors also point out that there are variations on this expert-based pattern.…”
mentioning
confidence: 99%